SISTEM INFORMASI PERSEDIAAN SUKU CADANG MENGGUNAKAN MODEL PROSES SCRUM - Raditya Ditto Aryaputra; Kristoko Dwi Hartomo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Inventory of goods is one of the important roles in a spareparts company. So that, spare inventory stock data from various vehicle manufacturers must also be kept up to date. However, in its business process, Carfix Salatiga currently still uses manual methods in managing and reviewing its spareparts inventory, so there is often a mismatch between the stock in the warehouse and the stock in the system. This is certainly an obstacle to the business process of Carfix Salatiga. Based on the description of the problem, a spare parts inventory information system was formed as a place for managing spare parts stock at Carfix Salatiga. The method that will be used in this design is the Scrum method. This method was chosen because it is flexible to changes in the needs of the existing system, and does not require many team members to build this system. The Scrum method has several stages, namely Product Backlog, Sprint Backlog, Daily Scrum and Sprint Review. The results obtained are in the form of a web-based inventory information system that can regulate the amount, update, delete, and place an order for spare parts to the central party so that it can make it easier for employees to digitally manage the availability of spare parts